Ընկերագիրք-հուշամատյանի ժանրը ԺԶ-ԺԹ դդ. Է. Քեմփֆերի Album amicorum-ի օրինակով - Աղաբեկյան, Լիանա (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Since the 16th century in a number of German universities, the so-called genealogical books, which were also known as album amicorum-the book of the friendship, are in use. During that period, students and scholars took small notebooks with blank pages with them during their travels, where their friends, acquaintances, or notable people they met along the way left their notes. Taking as an example the German scientist E. Kaempfer's similar work, the structure of album amicorums, the methodology of their formation, the influence of significant historical events of the time on them, as well as the role of friend-books as a reliable source in the coverage of various historical events have been analyzed in the following article.
Keywords: Դիվանագիտության պատմություն